Usefulness of the Simultaneous Acquisition of Spatial Harmonics Technique During MRI of the Shoulder - Magee, Thomas; Shapiro, Marc; Williams, David; Ramnath, R. Richard; Simon, Jeffrey (American journal of roentgenology (1976), 2003)
The simultaneous acquisition of spatial harmonics (SMASH) technique is a parallel imaging technique that uses fewer echoes than conventional techniques to obtain the desired resolution. Production of images occurs more quickly with parallel imaging than with conventional imaging. This study assesses the usefulness of the SMASH technique for MRI of the shoulder. SUBJECTS AND METHODS. Five experienced musculoskeletal radiologists prospectively interpreted MRIs of the shoulder in 50 consecutive patients. All patients underwent a complete MRI examination of the shoulder on a 1.5-T commercially available scanner. Axial fat-saturated proton density-weighted, coronal T1-weighted, and coronal and sagittal fat-saturated T2-weighted sequences were performed. Patients also underwent SMASH T2-weighted imaging in the coronal and sagittal planes. Coronal and sagittal SMASH T2-weighted imaging took approximately 50% as long to complete compared with conventional T2-weighted imaging. Each radiologist interpreted MRIs of the shoulder without knowing whether the images were obtained using the SMASH or the fat-saturated T2-weighted technique. Twenty-eight of the 50 patients also underwent subsequent arthroscopy, and the results were compared with MRI interpretations based on SMASH and fat-saturated T2-weighted images. We found no intraobserver variability between the interpretations of SMASH imaging and the interpretations of fat-saturated T2-weighted imaging. Of the 28 patients who also underwent subsequent arthroscopy, 19 were found to have full-thickness supraspinatus tendon tears and nine had superior labral anterior-to-posterior lesions. All arthroscopic findings correlated with prospective MRI interpretations. SMASH imaging allows significant time savings compared with fat-saturated T2-weighted MRI. We found that the use of the SMASH technique did not affect the MRI interpretation or the clinical outcome of patients.